2023
DOI: 10.54910/sabrao2023.55.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Heritability, and Genetic Gain in Sweet Potato (Ipomoea Batatas L. Lam) for Agronomic Traits

Abstract: The study aimed to estimate the genetic variability, heritability, and genetic advance in the existing sweet potato (Ipomoea batatas L. Lam) populations for growth and yield traits in Peninsular Malaysia. The experiment transpired in 2020 at the Centre of Excellent Tuber Crops Research, Malaysian Agricultural Research and Development Institute (MARDI), Bachok, Kelantan, Malaysia. A total of 39 sweet potato genotypes studied consisted of introduced hybrids from the International Potato Center (CIP), Peru, Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Unlike the case with plantlets in the TIS Bioreactor culture, even with a fast metabolic rate, the size of the culture container can balance, which was taller and broader and equipped with an aeration system, with the plantlets not experiencing stress from lack of oxygen; thus, the initial growth of plantlets focused more on the apical shoots. Earlier works have proven that plantlets in TIS Bioreactor culture have higher stem morphology than plantlets in conventional culture systems (Nurul-Afza et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the case with plantlets in the TIS Bioreactor culture, even with a fast metabolic rate, the size of the culture container can balance, which was taller and broader and equipped with an aeration system, with the plantlets not experiencing stress from lack of oxygen; thus, the initial growth of plantlets focused more on the apical shoots. Earlier works have proven that plantlets in TIS Bioreactor culture have higher stem morphology than plantlets in conventional culture systems (Nurul-Afza et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Lembayung can be harvested as early as 104 days. Full details of the said research can be found in the article published by Nurul-Afza et al (2023) titled: "Nurul-Afza K, Aziz A, Thiyagu D, Shahrilnizam JM (2023). Genetic variability, heritability, and genetic gain in sweet potato (Ipomoea batatas L. Lam) for agronomic traits.…”
mentioning
confidence: 99%